Biomimetic synthesis of carthamin, a red pigment in safflower petals, via oxidative decarboxylation. (7th August 2020) - Abe, Yuka; Sohtome, Takuo; Sato, Shingo
Abstract: Carthamin, a natural red pigment derived from safflower, was discovered centuries ago and has been utilized in several industries such as dye, food coloring, and natural medicine industries. Although it has been used since Egyptian times, its structural features were only determined in the mid‐1900s when pioneering studies were conducted to elucidate the carthamin structure and assign its stereochemistry. Reproducing the complex biosynthesis of carthamin has been a common research goal since then. However, this has been rendered complex because of the unstable precursors and low yields from the multiple steps involved in the synthesis. Herein, we report the total synthesis of carthamin via a four‐step procedure using ( S )‐ C ‐ β ‐D‐glucosylquinochalcone as the starting compound. The synthesis involves mild conditions, short reaction time, and readily available compounds. After de‐ O ‐methylation, condensation, oxidative decarboxylation, and saponification, carthamin was obtained in an overall yield of 9.5% through the proposed method. Abstract :